Chemical Decorations of “MARs” Residents in Orchestrating Eukaryotic Gene Regulation - Roychowdhury, Tanaya; Chattopadhyay, Samit (Frontiers in Cell and Developmental Biology, 2020)
Genome organization plays a crucial role in gene regulation, orchestrating multiple cellular functions. A meshwork of proteins constituting a 3D matrix help in maintaining the genomic architecture. Sequences of DNA that are involved in tethering the chromatin to the matrix are called Scaffold/Matrix Attachment Regions (S/MARs) and the proteins that bind to these sequences and mediate tethering are termed Scaffold/Matrix Attachment Region Binding Proteins (S/MARBPs). The regulation of S/MARBPsis important for cellular functions and is altered under different conditions. Limited information is available presently to understand the structure function relationship conclusively. Although all S/MARBPs bind to DNA, yet their context and tissue specific regulatory roles cannot be justified solelybased on the available information on their structures. Conformational changes in a protein lead to changes in protein-protein interactions (PPIs) that essentially would regulate functional outcomes. A well-studied form of protein regulation is post-translational modification (PTM).It involves disulphide bond formation, cleavage of precursor proteins and addition or removal of low molecular weight groups leading to modifications like phosphorylation, methylation, sumoylation, acetylation, PARylation, ubiquitination etc. These chemical modifications lead to varied functional outcomes by mechanisms like modifying DNA-protein and protein-protein interactions, altering protein function, stability, and crosstalk with other PTMs regulating subcellular localisations.S/MARBPs are reported to be regulated by PTMs thereby contributing to gene regulation. In this review, we discuss the current understanding, scope,disease implications and future perspectives of the diverse PTMs regulating functions of S/MARBPs.